The Evolution of Hollywood's Calculated Blockbuster Films: Blockbusted - Ross, Alexander (Lexington Books, 2023)
In this book, Alexander Ross highlights how creative entrepreneurs saved the Hollywood studios in the 1970s by establishing the calculated blockbuster, consisting of key replicable markers of success, as Hollywood's preeminent business model. Ross demonstrates how visionary individuals such as Coppola, Spielberg, Lucas, and Zemeckis helped create the modern, calculated blockbuster business model (BBM). However, with the rise of streaming giants and the studios struggling to compete, many consumers of entertainment now elect to partake from the comfort of their homes, making the difference between “cinema” and “television” anachronistic. Revisiting the history of those 1970s blockbusters and their ongoing impact on contemporary filmmaking, Ross offers distinct analysis on whether the calculated blockbuster can continue to lead, or if the streamers will continue to generate their own content and, eventually, fully control the dissemination process. For scholars and students in film, pop culture and business along with aspiring filmmakers, screenwriters, producers and executives, the book will be a valued resource.